2021
DOI: 10.3390/jpm11111228
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Prognostic Value of a Novel Hematologic Marker Fibrinogen-to-Lymphocyte Ratio in Head and Neck Adenoid-Cystic Carcinoma

Abstract: Many patients with adenoid-cystic carcinoma (ACC) experience an indolent course of disease over many years but face late recurrence, and long-term survivors are rare. Due to its infrequent occurrence, it is hard to predict outcome in these patients. The fibrinogen-to-lymphocyte ratio (FLR) was recently proposed as an outcome prognosticator in different cancer entities. We aimed to investigate its prognostic relevance in patients with head and neck ACC. This retrospective analysis was performed including all pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…21 FLR, combined with hemagglutination and inflammation markers, have a potential prognostic value in different types of cancers, such as non-small cell lung cancer, esophageal cancer, liver cancer, and head and neck adenoid cystic carcinoma. [16][17][18][19] In addition, Huang et al found that a high FLR level was a risk factor for peritoneal metastasis in GC. 20 The current study first reported the association between FLR and LNM in patients with AGC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 FLR, combined with hemagglutination and inflammation markers, have a potential prognostic value in different types of cancers, such as non-small cell lung cancer, esophageal cancer, liver cancer, and head and neck adenoid cystic carcinoma. [16][17][18][19] In addition, Huang et al found that a high FLR level was a risk factor for peritoneal metastasis in GC. 20 The current study first reported the association between FLR and LNM in patients with AGC.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it could be a predictor of peritoneal metastasis in GC. [16][17][18][19][20] However, there are no relevant reports focusing on the association between FLR and LNM in patients with GC. Therefore, the current study aimed to assess the predictive value of FLR in LNM in patients with clinically node-negative (cN0) AGC.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it may reflect the interaction between inflammation and clotting in cancer ( 16 ). FLR has been shown to assess tumor prognosis in carcinoma of stomach ( 15 ), esophagus cancer ( 16 ), non-small cell lung cancer ( 17 ) and head and neck adenoid-cystic carcinoma ( 18 ). In particular, higher FLR values were associated with poorer outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphocytes are important antineoplastic factors, which play a significant role in cancer-specific immune response ( 14 ). Recently, a novel prognosticator fibrinogen-to-lymphocyte ratio (FLR) has been proposed, which has been proved to evaluate the prognosis in gastric cancer ( 15 ), esophageal cancer ( 16 ), non-small cell lung cancer ( 17 ) and head and neck adenoid-cystic carcinoma ( 18 ). However, there is no study on the predictive performance of NLR and FLR in CRA recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer deregulates the immune cells within the tumor microenvironment and systemically, with first deregulations being observed one year prior to diagnosis [24]. To quantify and correlate such deregulations of the immune system with the prognosis and survival of cancer patients, several immune-related markers based on blood cell counts have been described, such as neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and lymphocyte-to-monocyte ratio (LMR) [25][26][27][28]. The predictive value of LMR has been reported in different malignancies [29][30][31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%